IBD 9 Research priorities in digital technology for adolescents and young persons with Inflammatory Bowel Disease: a James Lind Alliance Priority Setting Partnership. (12th September 2022) - Rao, Arati; Wong, Charlotte; Kalli, Antony; Manson, Jess; McLaughlin, John; Younge, Lisa; Kammermeier, Jochen; Lee, Gemma; Gasparetto, Marco; Shaji, Seb; Wakeman, Ruth; Ainley, Rachel; et al.
Abstract : Background: Digital healthcare (DHC) is a rapidly expanding area of healthcare and offers significant opportunities to transform Inflammatory Bowel Disease (IBD) care. DHC cover a wide range of technologies, including and not exclusive to apps, podcasts, websites, social media and patient controlled electronic medical platforms. Application digital technology (DT) in clinical practice should be supported by research evidence. A Priority Setting Partnership (PSP) was set up in collaboration with the James Lind Alliance (JLA), a non-profit organisation, to prioritise research topics that young people with IBD, their carers, and their clinicians consider important for evidence-based implementation of DT in IBD. Aim: To create a survey designed to identify the unanswered questions or evidence uncertainties in the use of DT for adolescents and young persons with IBD. Methods: PSP meetings were attended by key stakeholders as a Steering Group (SG): paediatric and adult gastroenterologists with an interest in adolescent and young person care from BSPGHAN and BSG respectively, IBD clinical nurse specialists, representatives from the IBD charities CICRA and CCUK and patient and parent representatives. The survey was designed through an iterative process at a series of meetings. The survey was considered complete when there was saturation of changes and the approval by all stakeholders. Readability was assessed by the Flesch-Kincaid Reading Ease test (a measure of average sentence length average number of syllables per word) and Flesch-Kincaid Grade Level test on Microsoft Word. Methods of dissemination were discussed and agreed. Results: The final survey consists of three sections. The first captures roles and connection of IBD to the individual completing the survey. The second invites participants to submit questions about DT in two areas: DT to support their condition and improve IBD care, and DT to improve communication with the healthcare team. Questions are open-ended to allow participants to elaborate on their answers. Due to the vast range of DT and potential questions, examples were provided to assist individuals with answering, including the example of a mobile app for recording symptoms and disease activity. The final section for demographic data is optional and will not be linked to responses in sections 1 or 2. Finally, participants are invited to be involved after the survey closes to help with further stages in the prioritisation process. The final survey is shown in figure 1. The Reading ease test score is 61 (good scores 60 to 70) and Flesch-kinaid grade level is 8.1 (optimal scores 7.0 to 8.0). The survey was approved by the patients within the SG. Conclusion: A SG with wide representation for a PSP on DT in IBD was created. As a first step to identify unanswered questions or uncertainties, a readable survey was developed. Research priorities will be identified using the JLA methodology and these will galvanise research on DT to improve disease outcomes and quality of life. DIGITAL TECHNOLOGY FOR ADOLESCENTS AND YOUNG PERSONS WITH INFLAMMATORY BOWEL DISEASE A Priority Setting Partnership (PSP) in collaboration with the British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN), British Society of Gastroenterology (BSG) and the James Lind Alliance (JLA) WHO ARE WE?: We are a group of patients, carers, healthcare professionals and researchers who are passionate about improving the care and quality of life of people living with inflammatory bowel diseases (IBD) such as ulcerative colitis and Crohn's disease. Together, we are collaborating on a project called a Priority Setting Partnership (PSP), to identify the top 10 research priorities for digital technology in adolescents and young persons with IBD. WHAT ARE WE DOING?: There are huge opportunities to transform IBD care with digital technologies, but we need to understand the impact that technologies will have and how to best use them. Digital technologies may include apps, podcasts, websites, social media and patient controlled electronic medical platforms. We are asking people up to and including the age of 25 who are affected by IBD; their families, carers and friends; health and social care professionals to help us identify the top 10 questions that need to be answered by research in this area. WHY DO WE NEED YOUR HELP?: We would like to hear from you if you are: an adolescent or young person up to and including the age of 25 with IBD a parent, carer or friend supporting an adolescent or young person with IBD a health or social professional involved in the care of IBD patients Your views will ensure that we focus on the needs of adolescents and young persons living with the condition and guide future research. WHAT DO I HAVE TO DO?: We are asking you to complete a short 10-minute survey. You don't have to be an expert in technology to take part. Ask us questions about the use of digital technologies based on your experience of living with IBD or supporting someone with the condition. WHAT HAPPENS AFTER THE SURVEY?: We will look at all the questions that have been asked in the survey and check that they align with this project. For the questions that have not been answered already by research, we would welcome you would help to put these into order of priority. Please leave your contact details at the end if you wish to be involved in this part. Finally, we will come up with a list of the top 10 research priorities which will be publicised to researchers and organisations that fund IBD research. WHAT WILL HAPPEN WITH MY INFORMATION?: By taking part in this survey, you give us consent to use your anonymized answers and publish these in our project report. We take your privacy seriously so we will not be able to personally identify you. You may also leave contact details at the end if you would like to continue to help with this project (optional). Personal contact details will be kept confidential. THERE ARE THREE SECTIONS TO THIS SURVEY: Section 1: This asks about who you are to help us understand your role and how you're connected with IBD. Section 2: We would like you to ask questions about the use of digital technology in 2 broad areas. You may wish to focus on just one area or both: Questions about digital technologies to support your condition and have the potential to improve IBD care. These technologies help your healthcare team with making decisions about diagnosis, treatment, and clinical care. They may also help you self-manage IBD, promote healthier ways of living and monitor your progress. Examples include mobile apps for recording your symptoms and disease activity or provide information. Questions about the use of digital technologies to improve communication with your healthcare team. These technologies help to improve the two-way communication between you and the health professionals who look after you. Examples included instant messaging portals and video consultations that link you to healthcare teams. Section 3 (optional): This asks for additional background information about you to help us understand who you are and to ensure that we have captured a range of different experiences. These answers will not be linked to your responses in section 1 and 2. SECTION 1: ABOUT YOU: It is important to know who you are, the person filling in the form, and how you are connected to IBD. Which of the following describes you best? □ I am an adolescent or young person with IBD □ I am a parent or have experience as a carer of an adolescent or young person with IBD □ I am a family member of an adolescent or young person with IBD □ I am a friend of an adolescent or young person with IBD □ I am a healthcare professional who looks after adolescents or young persons with IBD □ I am a member of an organisation or charity representing persons with IBD □ Other – please state…………….. SECTION 2: YOUR QUESTIONS: Write down 3 questions that you would like to see answered about the use digital technology in inflammatory bowel disease. This can be in the form of a sentence or a question. You do not have to fill in all of the sections if you don't want to. My first question/comment My second question/comment My third question/comment Please write down any other questions/concerns in the box below if you'd like to SECTION 3: ADDITIONAL INFORMATION ABOUT YOU (OPTIONAL): This optional but it is important to understand who is filling out the form to ensure that we have collected views from a range of people with varied experiences. 1. What is your age? □ <16 □ 16–25 □ 26–39 □ 40–59 □ 60–79 □ 80+ □ I prefer not to say 2. Which of the following best describes your gender? □ Boy/man □ Girl/woman □ Non-binary □ I prefer not to say □ I prefer to self-describe, please state………. 3. What is your ethnic group? Asian or Asian British □ Bangladeshi □ Chinese □ Indian □ Pakistani □ Any other Asian background, please describe………….. Black/African/Caribbean/Black British □ African □ Caribbean □ Any other Black/African/Caribbean background, please describe…… Mixed/Multiple ethnic groups □ Asian and White □ Black Caribbean and White □ Black African and White □ Any other mixed/Multiple ethnic background, please describe………. White □ English/Welsh/Scottish/Northern Irish/British □ Gypsy or Irish Traveller □ Irish □ Any other White background, please describe…….. Any other ethnic group □ Arab □ Any other ethnic group, please describe………… □ Prefer not to say 4. Where do you live? □ England □ Wales □ Scotland □ Northern Ireland □ I prefer not to say WOULD YOU LIKE TO HELP US WITH THE NEXT STEP?: Once the survey has closed, we would like to get back in touch with the people who completed this survey for help with collating research questions into order of importance or urgency. If you would like to take part in this stage, please add your contact details below. Thank you for completing the survey. If you have any questions or would like any further information, please contact:………………………………